2021
DOI: 10.1038/s41372-021-00941-x
|View full text |Cite
|
Sign up to set email alerts
|

Self-directed video versus instructor-based neonatal resuscitation training: a randomized controlled blinded non-inferiority multicenter international study

Abstract: Objective To compare the efficacy of video-assisted self-directed neonatal resuscitation skills course with video-assisted facilitator-led course. Methods This multicenter, randomized, blinded, non-inferiority-controlled trial compared two methods of teaching basic neonatal resuscitation skills using mask ventilation. Groups of novice providers watched an instructional video. One group received instructor facilitation (Ins-Video). The other group did not (Self-Video). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…369 Basic Life Support A total of 14 studies were included, addressing both BLS knowledge and BLS skills after the intervention. 276,356,357,[359][360][361][362][363][364][365][366][367]370,371 Results were mixed, with some studies finding a benefit with blended learning and some studies finding no difference. Only 1 study found a statistically significant benefit for knowledge 363 and for skills 364 with a face-to-face approach only.…”
Section: Consensus On Sciencementioning
confidence: 99%
“…369 Basic Life Support A total of 14 studies were included, addressing both BLS knowledge and BLS skills after the intervention. 276,356,357,[359][360][361][362][363][364][365][366][367]370,371 Results were mixed, with some studies finding a benefit with blended learning and some studies finding no difference. Only 1 study found a statistically significant benefit for knowledge 363 and for skills 364 with a face-to-face approach only.…”
Section: Consensus On Sciencementioning
confidence: 99%
“…With the need for a shift to NFF formats of CPR education, different educational methods have been studied, including the use of video-based and virtual reality training, as well as e-learning modules [ 8 ]. Previous studies have shown that NFF education may not be inferior to FF [ 9 , 10 ] but may be insufficient for skill mastery [ 11 ]. For effective NFF learning, the self-learning ability of students should be evaluated and improved [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Assuming a significance level of α=0.05, a final-exam success rate (‘passed’) in both groups (ie, traditional instructor-led learning and self-directed learning) of 90% and a non-inferiority margin of ∆=10%, a sample size of 224 participants was calculated as necessary to establish the non-inferiority of the self-directed learning with an integrated learning video group with a power of 80%. This sample size is similar to previous studies 14–16. Due to high levels of personnel fluctuation in the department, block randomisation was performed in two stages.…”
Section: Methods and Analysismentioning
confidence: 93%
“…This sample size is similar to previous studies. [14][15][16] Due to high levels of personnel fluctuation in the department, block randomisation was performed in two stages. First, all clinical staff members able to participate in the study (n=260) 2) What specific knowledge related to the anaesthesia workstation is needed for an anaesthesia procedure?…”
Section: Sample Size Calculationmentioning
confidence: 99%